Hemifacial microsomia - Ullal, Sonali (Springer-Verlag, 2009)
Hemifacial microsomia (HFM) is a craniofacial disorder characterized by a wide spectrum of anomalies, including conductive hearing loss due to external and middle ear deformities [1]. Hemifacial microsomia is the second most common developmental craniofacial anomaly after cleft lip and palate. Diagnostic imaging is important for presurgical evaluation of patients with this anomaly; however the broad spectrum of abnormalies encountered in patients with hemifacial microsomia can be confusing [2]. We present a case of a hemifacial microsomia in 12 year old male.